Ginsenoside Rc attenuates myocardial ischaemic injury through antioxidative and anti-inflammatory effects. (31st December 2022) - Shi, Lei; Fu, Wenwen; Xu, Huali; Li, Shihui; Yang, Xinyu; Yang, Wei; Sui, Dayun; Wang, Quanwei
Abstract: Context: Panax ginseng C. A. Meyer (Araliaceae) is a famous Asian medicine. Ginsenoside Rc is a component isolated from Panax ginseng . Objective: This study evaluates the effect of ginsenoside Rc on myocardial ischaemic injury. Materials and methods: Male Swiss mice were subcutaneously injected with 50 mg/kg isoproterenol once a day for three days. Ginsenoside Rc (10, 20, or 40 mg/kg) was intragastrically administered 1 h after isoproterenol injection. The mice in the control group were subcutaneously injected with normal saline and intragastrically given 0.5% CMC-Na. CK-MB and troponin T were assayed. Histopathological examination of myocardium was conducted. The expression of Nrf2, GCLC, GCLM and HO-1 in heart tissues was evaluated by Western blot. Results: In myocardial ischaemic mice, ginsenoside Rc reduced the levels of CK-MB (197.1 ± 15.7, 189.9 ± 19.0, 184.0 ± 14.4 vs. 221.6 ± 27.9) and troponin T (10.3 ± 1.7, 9.5 ± 1.3, 8.7 ± 1.7 vs. 13.4 ± 2.4). Ginsenoside Rc attenuated the necrosis and inflammatory cells infiltration in myocardium. Furthermore, ginsenoside Rc not only decreased the contents of MDA, TNF-α but also increased GSH level in the heart tissues. The expression of Nrf2, GCLC, GCLM and HO-1 was significantly increased in the animals treated with ginsenoside Rc. ML385, an Nrf2 inhibitor, blocked partially the ginsenoside Rc-mediated cardioprotective effect. Ginsenoside Rc attenuated myocardial ischaemic injury in mice, which may be, in part, through its antioxidative and anti-inflammatory effects. Conclusions: This study indicated that ginsenoside Rc might be a novel candidate for treatment of myocardial ischaemia.